PRAFORMULASI dan EVALUASI SEDIAAN KAPSUL DARI JAHE MERAH (Zingiber officinale) sebagai ANTIDISMINORHEA - Isma Oktadiana (MEDFARM: Jurnal Farmasi dan Kesehatan, 2022)
Red ginger is a tuber rhizome that grows wild in Indonesian soil and is often used as medicine. This study aims to develop and test red ginger (Zingiber officinale) extract capsules. Red ginger extract (active component), corn starch (filler), Vivapur 101 (adsorbent), Aerosil (absorbent), Talc (glidan), and magnesium stearate are among the constituents in this product (lubricant). The purpose of this study was to develop and test red ginger extract capsules. The results showed that the weight uniformity test for capsule preparations met the criteria for the average weight and did not deviate, and the disintegration time test for capsules met the requirements of less than 15 minutes.